2020
DOI: 10.1124/mol.119.116590
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Polyadenylation of ABC Transporters of the C-Family (ABCC1, ABCC2, ABCC3) and Implications on Posttranscriptional Micro-RNA Regulation

Abstract: ATP-binding cassette (ABC) transporters represent a large group of efflux pumps that are strongly involved in the pharmacokinetics of various drugs and nutrient distribution. It was recently shown that micro-RNAs (miRNAs) may significantly alter their expression as proven, e.g., for miR-379 and ABCC2. However, alternative mRNA polyadenylation may result in expression of 39-untranslated regions (39-UTRs) with varying lengths. Thus, length variants may result in presence or absence of miRNA binding sites for reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…The ABCC transporter, known as phase III enzymes, is one of the proteins that are significantly affected by posttranscriptional regulation. Especially, micro-RNAs(miRNAs) extensively affect their protein level through interaction with target mRNA [ 38 ]. Previous research reported B[a]P induces the mRNA expression of ABCCs, while inhibiting the protein level and function of ABCC transporters [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ABCC transporter, known as phase III enzymes, is one of the proteins that are significantly affected by posttranscriptional regulation. Especially, micro-RNAs(miRNAs) extensively affect their protein level through interaction with target mRNA [ 38 ]. Previous research reported B[a]P induces the mRNA expression of ABCCs, while inhibiting the protein level and function of ABCC transporters [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whole cell lysates and immunoblotting. Whole cell lysates and immunoblotting were performed as previously described (17,23,24) Cell adhesion assay. Corning Matrigel basement membrane mix (VWR) was thawed overnight at 4˚C.…”
Section: Genome-wide Expression Analysismentioning
confidence: 99%
“…Several adenosine triphosphate (ATP)-dependent proteins, such as the ATP-binding cassette (ABC) transporter superfamily, have been associated with drug resistance, metabolism, and toxicity [ 111 ]. Several polymorphisms of the main ABC transporters of P-glycoprotein ( MDR1 , ABCB1 ) and multiple resistance-associated protein 2 ( MRP , ABCC2 ) influence drug bioavailability and clinical response [ 112 , 113 ]. Alterations in ABC transporter efflux could limit central distribution of many psychotropic drugs, such as CBZ [ 114 ].…”
Section: Genetic Polymorphisms Of Drug Transporters and Cbz/vpa Rementioning
confidence: 99%